Isolation in studio music teaching: The secret garden - Bennett, Dawn; Burwell, K.; Carey, G. (Sage Publications, 2017)
In comparison with classroom settings that are more accessible to the scrutiny of researchers and institutional monitoring, the one-to-one setting of instrumental and vocal studio teaching has been described as a ‘secret garden’. The physical isolation of the music studio has deep roots within the traditions of apprenticeship and embodies aspects of conservatoire culture that are sometimes carried over into other musical styles. With a focus on higher education, this paper explores the nature and significance of isolation for the studio, alongside some of the benefits, limitations, and challenges that it offers. The authors contend that the physical disposition of the studio within the institution gives implicit support to the attitudes and assumptions that sustain traditional approaches to music performance teaching, and that making them explicit can help to open those approaches to further challenge, review and development.